Pensionable age vs cross-country diversity of economic activity of the near-elderly - Filip Chybalski (Journal of Economics, Finance and Administrative Science, 2021)
Purpose: The purpose of this paper is to examine whether cross-country differences in pensionable age explain such differences in economic activity of people at near-retirement age. Design/methodology/approach: The empirical study uses regression models for macro-panel encompassing 21 European countries in the period 2008-2014. Findings: Empirical results indicate that pensionable age is a determinant of cross-country differences in employment rate in the near-retirement age group, and less a factor differentiating average effective retirement age. It turns out that other factors matter, including salaries and wages as percentage of GDP (treated as a proxy for the occupational composition of populations across the countries studied), self-employment, participation in education and training, or self-perceived health. Social implications: The problem of economic activity at the near-retirement age is complex and cannot be limited to legal regulations concerning pensionable age. The policy aiming at stimulating the economic activity of the near-elderly should include actions on many sides including labour market, pension system, education, training, or health care. Originality/value: The results complement studies based on the single-country approach and demonstrate that pensionable age does not account for cross-country differences in terms of average effective age of retirement when controlling for other factors. Moreover, factors differentiating effective retirement age and employments rates across countries studied are not similar.
Keywords: 330; Age management; Comparative study; Labour market; Pensions; Population aging; Retirement